2002
DOI: 10.1161/hs0302.103661
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Intima-Media Thickness and Lacunar Versus Nonlacunar Infarcts

Abstract: Background and Purpose-Increases in the thickness of the intima and media of the carotid artery have been associated with an increased risk of myocardial infarction and stroke in subjects without a history of cardiovascular disease. Lacunar infarcts, one of the most common subtype of ischemic stroke, show unique pathological and clinicoradiological characteristics. The present study examines the relationship between vascular risk factors, including carotid artery intima-media thickness (IMT), and lacunar versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
79
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 61 publications
8
79
1
7
Order By: Relevance
“…Cupini et al (2002) 11 showed smoking among 35.4% and 33.2% of patients with lacunar and non-lacunar stroke respectively which was not significant (p>0.05), but was consistent with the current study. Similarly, Tejada et al (2003) 20 showed smokers were almost similar between two groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cupini et al (2002) 11 showed smoking among 35.4% and 33.2% of patients with lacunar and non-lacunar stroke respectively which was not significant (p>0.05), but was consistent with the current study. Similarly, Tejada et al (2003) 20 showed smokers were almost similar between two groups.…”
Section: Discussionsupporting
confidence: 90%
“…The arterial pathology of lacunar infarction is based largely on Fisher's meticulous clinicopathological studies, in which he serially dissected the vascular supply of a total of 68 lacunar infarcts in 18 postmortem brains 10 . To be defined as a lacunar stroke by MRI, the following criteria had to be met: (1) be round or oval in shape; (2) measure <1.5 cm in diameter; (3) be located in the typical territory supplied by deep or superficial small perforating arteries; (4) not be in cortical territories; and (5) not have the morphological and topographical distribution consistent with partial internal border-zone infarcts 11 .…”
mentioning
confidence: 99%
“…this suggests that the progression of arteriosclerotic change in the brain was paralleled by systemic atherosclerosis and conversely that assessment of systemic atherosclerosis could predict latent damage to the brain, almost similar findings reported by various investigators from different countries. 3,4,5,11,12,13,14 The characteristics of SCI lesions were similar to the results of other studies. 13,15,16,17 that is, they were usually smaller than 1cm,were mostly in the basal ganglia (P<0.01) and had a higher incidence in right cerebral hemisphere (P<0.05) signified non-dominant hemisphere predominance for SCI.…”
Section: Discussionsupporting
confidence: 87%
“…Similar type of findings were also observed by other investigators. [3][4][5][12][13][14][15]21 age, hypertension and plaque score strongly and independently correlated with the occurrence of SCI of brain, compatible with results of other studies. 22,23,24 Conclusion Silent cerebral infarction (SCI) detected incidentally by MRI is considered the preliminary stage of accidental stroke and assumed to be secondary to atherosclerotic vascular disease (ASVD).…”
Section: Discussionsupporting
confidence: 84%
“…Impact of gender on 24-h ambulatory BP and target organ damage V Kotsis et al et al 48 reported that IMT values of common carotid artery were significantly higher in patients with non-lacunar stroke than those with lacunar stroke and also in control subjects. Studies also suggested that there is a significant correlation between the ultrasound measurements of IMT of the carotid arteries and coronary artery lesions.…”
mentioning
confidence: 99%